PENGUKURAN PENGETAHUAN MAHASISWA TERHADAP DEMAM BERDARAH DAN UPAYA PENCEGAHAN DEMAM BERDARAH MELALUI PENABURAN SERBUK ABATE - Antara, Nyoman Yudi; Preharsini Kusuma, Ida; Bataragoa, Efrita (BESIRU : Jurnal Pengabdian Masyarakat, 2025)
Dengue fever (DBD) remains a major public health concern in Indonesia. Continuous prevention efforts are essential to reduce its incidence, including the implementation of Mosquito Nest Eradication (PSN) 3M Plus strategies. Additionally, the application of larvicide powders such as Abate to mosquito breeding sites has proven effective in controlling mosquito populations. This community service initiative aimed to reduce the presence of dengue vector mosquitoes by applying Abate powder and to evaluate students' knowledge regarding dengue prevention at the Faculty of Mathematics and Natural Sciences (FMIPA), Halu Oleo University. The application of Abate powder was successfully conducted, and a significant improvement in student knowledge was observed following educational counseling, as indicated by a Bayes Factor (BF₁₀) of 236.185.